Subcutaneous Implantable Cardioverter‐Defibrillator in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia: A Transatlantic Experience - Gabriela M. Orgeron; Aditya Bhonsale; Federico Migliore; Cynthia A. James; Crystal Tichnell; Brittney Murray; Emanuele Bertaglia; Julia Cadrin‐Tourigny; Pietro De Franceschi; Jane Crosson; Harikrishna Tandri; Domenico Corrado; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Despite growing use of the subcutaneous implantable cardioverter‐defibrillator (S‐ICD), its clinical role in arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) patients remains undefined. We aim to elucidate the cardiac phenotype, implant characteristics, and long‐term efficacy regarding appropriate therapy and complications in ARVC/D patients with an S‐ICD implant. Methods and Results A transatlantic cohort of ARVC/D patients who underwent S‐ICD implantation was analyzed for clinical characteristics, S‐ICD therapy, and long‐term outcome including device‐related complications. The cohort included 29 patients (52% male, 76% probands, 59% with ARVC/D‐associated mutation, 59% primary prevention [no prior sustained ventricular arrhythmias], and 45% first‐generation S‐ICD devices). At implant, all inducible patients (27/29) had conversion of induced ventricular fibrillation. Two patients (7%) had superficial infections of the incision site that were treated conservatively. Over a median follow‐up of 3.16 years (interquartile range: 2.21–4.51 years), all episodes (6 patients, 4% per year) of sustained ventricular arrhythmias were appropriately detected and treated. Six patients (21%) experienced 39 inappropriate shocks, with 3 requiring device explantation. Oversensing of noncardiac signal (n=4; especially myopotentials) and cardiac signal (n=4) was the most frequent etiology. No lead or device dislodgement, infection, skin erosion, or explantation related to need for antitachycardia pacing was noted. Conclusions S‐ICD can effectively treat both induced and spontaneous ventricular arrhythmias in patients with ARVC/D. The rate of inappropriate shocks, although considerable, is comparable to that in ARVC/D patients treated with transvenous ICDs. When they occurred, inappropriate shocks were primarily due to cardiac and, uniquely, noncardiac oversensing. We suggest potential strategies for minimizing inappropriate therapy.